Drivers of hydroperiod in ephemeral and permanent wetlands - Hilger, Anna (University of Wisconsin--Stout. Office of Research and Sponsored Programs, 2017)
Wetlands serve as a habitat for many different plant and animal species that rely on various hydroperiods to survive. Understanding the influences on hydroperiod may help to compensate for any future loss or changes in hydroperiod due to environmental change. Aspects of wetland hydroperiod (min/max depth, seasonal range, mean periodic (six hours) fluctuation, and maximum periodic fluctuation) were related to explanatory geomorphic variables (surface area to volume ratio, basin size, wetland area, and elevation). Permanent (PW) and ephemeral pond (EP) hydroperiod characteristics were compared for wetlands in Chippewa County, Wisconsin. Pressure transducer data loggers were placed in paired PWs and EPs to collect water depth data. In EPs, canopy cover was negatively related to maximum depth, because trees decrease water depths through interception and/or transpiration. Seasonal range was positively correlated with EP area and negatively correlated to peat depth. Larger EPs may have had a larger seasonal range because they both captured and evaporated more water. EPs in larger basins had both higher mean and maximum periodic fluctuations, because larger basins result in more runoff from precipitation. Range and maximum fluctuation were significantly higher in EPs than PWs. Mean periodic fluctuation was not significantly different because PWs were both filling up and evaporating whereas EPs were mostly evaporating with occasionally dramatic increases due to precipitation. PWs that were smaller and lower in elevation with smaller basins tended to have more variable hydroperiods than larger PWs due to a lack of water storage in the basin.
Research article with map, graphs, and tables.
Keywords: hydroperiod; ephemeral ponds; Vernal pools; Wetlands